The effects of different exercises on weight loss and hormonal changes in women with polycystic ovarian syndrome: a network meta-analysis study - Fatemeh Motaharinezhad; Alireza Emadi; Motahareh Hosnian; Alireza Kheirkhahan; Ahmad Jayedi; Fatemeh Ehsani (BMC, 2024)
Abstract Background Polycystic ovarian syndrome (PCOS) is one of the most common endocrine illnesses. There is evidence that exercise training positively affects on improvement of the pathogenic factors in women with PCOS. On the other hand, some studies reported similar effects of aerobic and resistance exercises or no effect of exercises on the improvement of the pathogenic factors. The aim of the current study was to perform a network meta-analysis of RCTs to evaluate the efficacy of exercises on body mass index (BMI), hormone concentrations, and regular menstruation in women with PCOS. Methods The search was performed from databases of PubMed, Scopus, and Web of Science with the keywords of exercise, resistance exercise, aerobic exercise, endurance exercise, yoga, polycystic ovary syndrome, randomized controlled trial based on the CONSORT, BMI, sex hormone and regular menstruation from inception until April 15, 2022. Bayesian random-effects network meta-analyses were performed to calculate mean difference and 95% credible intervals. Results Out of 1140 studies, 19 were eligible for inclusion. The results showed that moderate-intensity aerobic exercise effectively reduces BMI compared to no intervention and Yoga. No other forms of exercise led to weight loss. Additionally, exercise had no impact on sex hormones and regular menstruation. It was concluded that moderate-intensity aerobic exercise is the most effective for reducing BMI in women with PCOS. Conclusions Due to the limitations regarding the small sample size and lack of subgroup and sensitivity analysis, the results of this study demonstrated that moderate-intensity, aerobic exercise is the most effective exercise for reducing BMI, while the other exercises were ineffective. Moderate-intensity aerobic exercise is suggested to decrease the BMI in women with PCOS. Systematic review registration This systematic review and network meta-analysis study was registered in PROSPERO (CRD42022324839).